Trade Liberalization and Firm Productivity: The Case of India - Topalova, Petia; Khandelwal, Amit (The Review of Economics and Statistics, 2011)
This paper exploits India's rapid, comprehensive, and externally imposed trade reform to establish a causal link between changes in tariffs and firm productivity. Pro-competitive forces, resulting from lower tariffs on final goods, as well as access to better inputs, due to lower input tariffs, both appear to have increased firm-level productivity, with input tariffs having a larger impact. The effect was strongest in import-competing industries and industries not subject to excessive domestic regulation. While we find no evidence of a differential impact according to state-level characteristics, we observe complementarities between trade liberalization and additional industrial policy reforms.